Creating a single-day travel itinerary for multiple tourism destinations in Kuala Lumpur using integer linear programming of travelling salesman problem / Muhammad Ayman Nor Isjamal Naser - Nor Isjamal Naser, Muhammad Ayman (2024)
This study presents a novel approach for creating a single-day travel itinerary with an optimal visit sequence for multiple tourism destinations in Kuala Lumpur. Leveraging the principles of integer linear programming and the traveling salesman problem (TSP), the research aims to address the challenge of efficiently organizing visits to various tourist attractions within a constrained time frame. The objectives encompass the identification of key tourism destinations based on visitors' preferences, the determination of the shortest travel times between these destinations using an integer linear programming model, and the establishment of a comprehensive travel itinerary with a specific visiting sequence. The methodology involves the utilization of the MTZ-TSP method and its integration into CPLEX to derive the best sequence for allocating time at each tourism destination. The findings of this research endeavor to offer a systematic and optimized approach for crafting travel itineraries, thereby enhancing the overall tourism experience in Kuala Lumpur.